Preference of saliva over other body fluids as samples for clinical and laboratory investigations among healthcare workers in Ibadan, Nigeria (2019)
The study aimed to assess the knowledge and practices of clinicians and laboratory scientists on the use of saliva for clinical or laboratory tests. This was a cross-sectional survey of health care workers (100 clinicians and 62 laboratory scientists) closely involved with specimen collection for clinical and laboratory investigation at two health facilities (secondary and tertiary) in Nigeria. Information was obtained from participants using pretested structured questionnaires. Data were analyzed with SPSS and level of significance set at p < 5%. The mean age of the study participants was 34.1 (±6.6) years. The majority (95.7%) knew saliva could be used for clinical/laboratory test. A higher proportion of laboratory scientists knew saliva could be used in diagnosing HIV (59.2%), oral diseases (88.7%), oro-facial tumors (64.4%) and genetic testing (94.5%) compared to (41%), (80%), (40%) and (80%), of clinicians respectively (p < 0.05). More clinicians (85%) indicated saliva as a good specimen for diagnosing systemic diseases compared with scientists (63%), p < 0.001. Saliva was the most comfortable/convenient body fluid to obtain from patients with more clinicians (80%) mentioning this than scientists (49.1%), p < 0.001. Twenty-six clinicians had used saliva for disease diagnosis (64%), treatment monitoring (28%) or research purposes (8%). Saliva sampling for research purposes was more prevalent among clinicians (p = 0.004). The majority of the health care workers knew the various uses and advantages of saliva as a specimen for clinical and laboratory investigation. However, few indicated previous use for clinical and laboratory investigation especially in the area of research